Biomechanical Evaluation of Human Allograft Compression in Anterior Cruciate Ligament Reconstruction. Issue 2 (16th February 2016) - Lord, Breck; Yasen, Sam; Amis, Andrew; Wilson, Adrian
Introduction: A common problem encountered during ACL reconstruction is asymmetry of proximal-distal graft diameter leading to tunnel upsizing and potential graft-tunnel mismatch. Human allografts are often oedematous, compounding this issue in the context of multi-ligament reconstructions. Tunnel upsizing reduces bone stock, increases the complexity of multi-bundle surgery and may compromise graft-osseous integration if cortical suspensory fixation is used. Graft compression provides uniform size, allowing easy passage into a smaller tunnel, potentially improving the 'press-fit' graft-osseous interaction whilst preserving bone stock. To our knowledge, no biomechanical evaluation of this increasing popular technique has been reported. Hypotheses: Graft compression would not cause any significant changes in the biomechanical properties of human allograft tendon that would be detrimental to the function of an ACL reconstruction. Compressed Bioclense® allograft will increase in size when soaked in Ringer's solution at 36° improving the 'press-fit' within the bone socket, decreasing micro-motion at the graft-osseous interface following ACL reconstruction. Method: In-vitro laboratory study. Sixteen samples of Bioclense® treated peroneus longus allograft were quadrupled into GraftLink constructs randomly divided into control and compressed groups. Cross-sectional area (CSA) was determined using alginate moulds and specimens immersed, under tension, in Ringer's solution at 36.5°. CSA was measured at 8 hours. A further 32 samples were randomised and evaluated under cyclic loading of 70N-220N (1020 cycles) followed by test to failure. A further 30 samples were quadrupled into GraftLink constructs and mounted within porcine femurs using suspensory fixation. High resolution videometer recorded motion at the graft-osseous interface under the same cyclic loading protocol. An independent samples t-test was used to compare changes in CSA whilst a one-way ANOVA was used for biomechanical end points. Results: CSA increased by 1.2 ± 0.04% and 16 ± 0.07% in control and compressed groups during joint simulation (P<0.05). Cyclic creep was 0.62 ± 1.22mm and 1.75 ± 0.97 (P>0.05), the Young's moduli were 617 ± 172 MPa and 708 ± 219 MPa (P>0.05) and ultimate tensile strength 85.2 ± 27.4 MPa and 89 ± 25.3 MPa (P>0.05) for the control and compressed groups respectively. Initial samples (n=4) show amplitude of cyclic motion of control and compressed ACL grafts in situ were 2.1mm (±0.6) and 1.9mm (±0.7) for control and compressed groups respectively. Conclusions: The process of graft compression does not have any detrimental effects upon Bioclense® treated allograft tendons. Following graft compression, these tendons significantly increase in size during intra-articular simulation promoting a 'press-fit' within the bone socket. Graft compression may significantly decrease micro-motion at the graft-osseous interface with further testing. Clinical Relevance: Graft compression is a biomechanically safe adjunct to ACL reconstruction when using Bioclense® treated allograft, aiding surgical technique and preserving bone stock.